Classical Theory In International Relations - JAHN, Beate (Cambridge, 2006)
Classical political theorists such as Thucydides, Kant, Rousseau, Smith, Hegel, Grotius, Mill, Locke and Clausewitz are often employed to explain and justify contemporary international politics and are seen to constitute the different schools of thought in the discipline. However, traditional interpretations frequently ignore the intellectual and historical context in which these thinkers were writing as well as the lineages through which they came to be appropriated in International Relations. This collection of essays provides alternative interpretations sensitive to these political and intellectual contexts and to the trajectory of their appropriation. The political, sociological, anthropological, legal, economic, philosophical and normative dimensions are shown to be constitutive, not just of classical theories, but of international thought and practice in the contemporary world. Moreover, they challenge